Marital Beliefs, Marital Virtues, and Neighborhood Cohesion as Predictors of Marital Satisfaction in Addis Ababa, Ethiopia: A Multilevel Analysis - Wondimu, Shimelis; Andualem, Tamirie (Innovation Journal of Social Sciences and Economic Review, 2024)
This study examines the role of marital beliefs, marital virtues, and neighborhood cohesion in marital satisfaction among 386 participants in Addis Ababa, Ethiopia. The study used a descriptive correlational study design. Participants were selected using multistage random sampling techniques, and data were collected using a questionnaire. Multilevel modeling was employed to analyze the data. Findings indicated that all marital beliefs, marital virtues, and neighborhood cohesion were positively and significantly associated with marital satisfaction. The findings from multilevel modeling showed that marital virtues and neighborhood cohesion significantly predicted marital satisfaction at both individual and neighborhood levels, whereas marital beliefs predicted marital satisfaction only at the individual level. Besides, marital virtues moderated the association between shared neighborhood cohesion and marital satisfaction, such that participants who reported lower marital virtues had a lower level of marital satisfaction when their neighbors experienced lower shared neighborhood cohesion. The interactive effect of shared marital virtues and marital beliefs can also influence marital satisfaction when participants reported low levels of marital belief and from a neighbor of fewer marital virtues; they tend to report low levels of marital satisfaction. The study concludes that the participants’ positive beliefs about marriage, marital virtues, and cohesive relationships with their neighbors positively influence their marital satisfaction. Marriage practitioners, policymakers, and community workers might benefit from this study. Limitations and future directions are also discussed.